PENYULUHAN GIZI SEIMBANG UNTUK MENINGKATKAN PENGETAHUAN IBU BALITA DI PERUMAHAN MARENDAL TERATAI III PATUMBAK KABUPATEN DELI SERDANG SUMATERA UTARA - Putri, Rizqi Nanda; Sitio, Sri Sudewi Pratiwi; Amirah, Nada; Tanjung, Lina Febriani; Azhary, Muhammad Rifqi; Sembiring, Efrata (INSTITUT KESEHATAN DELI HUSADA, 2025)
Balanced nutrition is a daily diet that contains nutrients in types and amounts that are appropriate to the body's needs, while still paying attention to food variety, physical activity, cleanliness, and ideal body weight. Based on Riskesdas data from the Ministry of Health regarding the Indonesian Nutritional Status (SSGI) in 2022, the stunting rate in Indonesia decreased by 2.8% from 2021 to 2022. This achievement is in accordance with the annual target of the Ministry of Health, which is around 2.7% per year. This study was conducted in November-December 2023 at the Marendal Teratai III Patumbak Housing Complex, Deli Serdang Regency, North Sumatra. The sample in this study was 20 mothers who had toddlers. The level of knowledge of mothers about toddler nutrition that was the most was a moderate level of knowledge, namely 11 people (55%) and a low level of knowledge, namely 7 people (35%), while the least was a high level of knowledge, namely 2 people (10%). Most of the mothers' knowledge about balanced nutrition in toddlers in the Marendal Teratai III Patumbak housing complex had sufficient knowledge about nutrition.